Thermal characteristics of the permafrost within an active rock glacier (Murtèl/Corvatsch, Grisons, Swiss Alps) - Vonder Mühll, Daniel; Haeberli, Wilfried (Journal of Glaciology, 1990)
ISSN:0022-1430 ISSN:1727-5652